To Think and Watch the Evil: The Turn of the Screw as Cultural Reference in Television from Dark Shadows to C.S.I. - Anna Viola Sborgi (Babel: Littératures Plurielles, 2012)
Since its first publication, Henry James’s The Turn of the Screw (1898) has always haunted the imagination of artists (Benjamin Britten, Jack Clayton, Amenábar) and has been widely used as a source for television narratives (Dan Curtis, US TV version starring Colin Firth, Tim Fywell). In serial productions, James’s story has been the object of extensive quotation and allusion, from the 1960 gothic soap opera Dark Shadows to the C.S.I. episode Turn of the Screw (Season 4, Episode 21). A milestone in literary history, the story now embodies a set of cultural references conveying different, complex meanings, which can only be disclosed in the light of contemporary forms of representing reality. The novella appeals to two apparently opposite tendencies in contemporary television: the morbid display of the real (C.S.I.) and the quest for the supernatural (Buffy The Vampire Slayer, among others). A line can be traced from Dark Shadows, the show that pioneered the genre, to contemporary horror soaps about vampires and supernatural phenomena. This paper shows the ways in which James’ sophisticated novella makes its way through popular culture, and how its constant ambiguous, dilemmatic interplay between reality and imagination can be related to the double-sided drive of the contemporary public towards hyper-reality and the supernatural.